Outranking methods: PROMETHEE I and PROMETHEE II - Shankha Shubhra Goswami (Foundations of Management, 2020)
This article highlights the application of the Preference Ranking Organization Method for Enrichment of Evaluations (PROMETHEE) I and II in selecting the best laptop model among six different available models in the market. Seven important criteria, that is, processor, hard disk capacity, operating system, RAM, screen size, brand, and color, are selected, based on which the selection process have been made. Analytic hierarchy process (AHP) is adopted for calculating the weightages of the seven criteria and PROMETHEE is applied to select the best alternative. PROMETHEE I provides the partial ranking and preferences of one model over another, whereas PROMETHEE II provides the complete ranking of the alternatives. From this analysis, Model 4 is coming out to be the best laptop model occupying the first position and Model 1 occupies the last position, thus indicating it as the worst model among the group. The objectives of this article are to select the best laptop model among six available alternatives and to understood the steps of both multiple criteria decision-making (MCDM) methodologies, that is, PROMETHEE and AHP, in details.
Keywords: C61; C83; D81; M11; 650; PROMETHEE I; PROMETHEE II; AHP; MCDM; laptop models